Serum folic acid: an effective indicator for arteriogenic erectile dysfunction - Feng, Xingliang; Mei, Yangyang; Xie, Pinpeng; Xing, Zhaoyu; Wang, Xiaogang; Cui, Li; Xu, Renfang (Frontiers in Endocrinology, 2023)
Background The present study is the first to explore the correlation between serum folic acid (FA) level and penile arterial peak systolic velocity (PSV) as measured via penile color Doppler ultrasonography (PDU), which directly reflects endothelial function in the penile artery. Materials and methods A total of 244 consecutive erectile dysfunction (ED) patients and 72 healthy controls, recruited from the Andrology department and the Healthy Physical Examination Center of our hospital, respectively, from June 2020 to April 2022, were included in the study. Serum FA was measured in ED patients and healthy controls, and PDU examinations were conducted for all eligible ED patients. The Pearson method was used to evaluate the correlation between FA levels and PDU parameters in ED patients. A receiver operating characteristic (ROC) curve analysis was also performed to calculate the sensitivity and specificity of these parameters for prediction of arteriogenic ED. Results After the PDU test, the average serum FA level among patients diagnosed with arteriogenic ED was 8.08 ± 2.64 ng/ml, lower than the average of 10.78 ± 2.87 ng/ml among healthy controls. There were no statistically significant inter-group differences on any basic parameters, including age, body mass index, fasting blood glucose, total cholesterol, and triglyceride. For further analysis, we divided the arteriogenic ED group into three subgroups by PSV range to compare serum FA levels among these subgroups. The mean FA levels in each of these groups were 5.97 ± 1.51ng/ml, and 8.21 ± 2.37ng/ml, and 10.55 ± 2.56ng/ml, while the corresponding PSV values were 15.75 ± 2.39cm/s, 23.53 ± 2.19cm/s, and 32.72 ± 1.64cm/s. Overall, a positive correlation between PSV and FA level was found among patients with arteriogenic ED (r=0.605, P<0.001). Furthermore, when FA level was used, with a cut-off value of 10.045 ng/ml, as a criterion to distinguish patients with arteriogenic ED from healthy controls, the area under the curve (AUC) was 0.772 (95% confidential interval: [0.696, 0.848]), for a sensitivity of 0.611 and specificity of 0.824. Conclusion Serum FA level is positively correlated with PSV in ED patients, and has the ability to distinguish patients with arteriogenic ED from healthy controls. Taking these findings together, FA deficiency should be regarded as an independent risk factor for arteriogenic ED.